The impact of Hallyu globalization on attitudes and behavior of Malaysians - Azmi Murad, Masrah Azrifah; Nasharuddin, Nurul Amelina; Roslan, Muhammad Amirul Asyraaf (UiTM, 2024)
This study investigates how Hallyu culture influences Malaysian attitudes and behaviours, focusing on K-pop, K-dramas, Korean culture, and style. Hallyu, or the Korean Wave, encompasses South Korean music, dramas, fashion, and cuisine, globally. By distributing surveys on social media platforms, the research gathered data from 219 respondents on demographics, Hallyu engagement, and consumption patterns among Malaysians. Results showed a strong preference for K-pop and K-dramas, with streaming platforms being the primary access method. Many respondents also embraced Korean cuisine, fashion, and beauty products influenced by Hallyu. The study highlights Hallyu's significant impact on Malaysian society and culture, emphasising varied engagement levels from digital consumption to active participation in cultural events. Future research could explore specific aspects like K-pop fandom using qualitative methods for deeper insights.